The influence of service quality provided by Melaka International Trade Centre Sdn. Bhd. (MITC) towards customer satisfaction / Mohd Fadzli Abdul Rahman - Abdul Rahman, Mohd Fadzli (Faculty of Business and Management, 2006)
Meeting, Incentives, Conventions, and Exhibitions (M.I.C.E.) is a new service industry in our country. Melaka International Trade Centre (MITC) is renowned for providing national and international convention and exhibition organizers with the highest standards of personal service and event facilities. Today, service quality among International Trade Centre has becoming more important in order for them to gain competitive advantage and satisfied their customers. The company have to manage its customer satisfaction very well because customer satisfaction can influence their performance and service quality. This study is done on the influence of service quality provided by Melaka International Trade Centre Sdn. Bhd. (MITC) towards customer satisfaction. The objectives of this study are to identify the elements of service delivery that can most influential to customer satisfaction and whether the customer satisfaction will correlate to quality of service. The study only focus on customers in Ayer Keroh, Melaka. The sample only consists of 100 customers as respondents. 100 sets of questionnaires were distributed but only 67 were returned. Based on the findings, most of the respondents felt satisfied with the services provided by the company. Statistical Package of Social Science (SPSS) version 12.0 is used to analyze the data in this study.